2000
DOI: 10.1097/00005392-200007000-00023
|View full text |Cite
|
Sign up to set email alerts
|

Long-Term Hazard of Progression After Radical Prostatectomy for Clinically Localized Prostate Cancer: Continued Risk of Biochemical Failure After 5 Years

Abstract: Although progression after radical prostatectomy usually occurs early, reflecting the impact of clinical under staging, a significant number of men, including those with organ confined cancers, will continue to have disease progression after 5 years. Patients undergoing radical prostatectomy should be subjected to long-term followup to allow the option of early intervention should progression occur.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
93
0
5

Year Published

2005
2005
2020
2020

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 79 publications
(99 citation statements)
references
References 22 publications
1
93
0
5
Order By: Relevance
“…Therefore, we were required to create ad hoc definitions for cancer-specific and other-cause mortality for the men who were lost to follow-up. However, in addition to making our definitions very conservative based on existing data, 9,[19][20][21] historic evidence supports the extremely low rates of prostate cancer mortality among men with low-risk disease. [8][9][10]14 In conclusion, we have demonstrated that the men with the most severe comorbidity in our cohort (ie, those with Charlson scores !3) were overtreated with aggressive treatment for low-risk prostate cancer in 54% of cases.…”
Section: Original Article 2064mentioning
confidence: 88%
“…Therefore, we were required to create ad hoc definitions for cancer-specific and other-cause mortality for the men who were lost to follow-up. However, in addition to making our definitions very conservative based on existing data, 9,[19][20][21] historic evidence supports the extremely low rates of prostate cancer mortality among men with low-risk disease. [8][9][10]14 In conclusion, we have demonstrated that the men with the most severe comorbidity in our cohort (ie, those with Charlson scores !3) were overtreated with aggressive treatment for low-risk prostate cancer in 54% of cases.…”
Section: Original Article 2064mentioning
confidence: 88%
“…1 However, a significant proportion of patients can experience disease recurrence and prostate specific antigen (PSA) progression is the earliest evidence of persistent or recurrent disease after primary therapy with curative intent. 2 In previously untreated patients with nonmetastatic PCa 150 mg bicalutamide monotherapy has been shown to be equivalent to castration in terms of the survival rate at a median followup of 6.3 years, offering quality of life (QOL) advantages with respect to sexual interest and physical capacity.…”
mentioning
confidence: 99%
“…Lokalize prostat kanseri nedeniyle Radikal Prostatektomi (RP) uygulanan olguların yaklaşık 1/3'ünde on yıl içinde nüks gelişmektedir (1,2). Nüksler operasyon yerindeki kalıntı subklinik hastalığa veya prostatektomi sırasında mevcut gizli metastatik hastalığa bağlı olup zaman içinde Prostat Spesifik Antijen'de (PSA) yükselme, lokal nüks veya uzak metastazlarla kendini gösterir.…”
Section: Introductionunclassified